'The Queen Mother and I': assimilation, contrast, and attitudes toward social groups - Haddock, Geoffrey; Carrick, Rachael (European journal of social psychology, 1999)
We examined whether social group attitudes are subject to context effects. It was hypothesised that manipulating the context in which a group exemplar was rendered accessible would produce different effects when subjects were subsequently asked to evaluate the exemplar's group. In our study, all subjects first expressed their opinion about the (popular) Queen Mother before indicating their attitude toward the British Royal Family. In the ‘non‐redundant’ condition, the two questions were structured such that the Queen Mother was expected to be included in individuals' representation of the Royal Family, leading to a high correlation between the two judgements and a favourable evaluation of the group. Conversely, in the ‘redundant’ condition, the questions were structured such that the Queen Mother was expected to be excluded from individuals' representation of the Royal Family, leading to a lower correlation between the judgements and a less favourable evaluation of the group. The results supported the hypothesis, and are consistent with the Schwarz and Bless (1992a,b) inclusion/exclusion model of assimilation and contrast. Copyright © 1999 John Wiley & Sons, Ltd.